EFEKTIVITAS PEMBERIAN EKSTRAK FERMENTASI BAWANG PUTIH (BLACK GARLIC) TERHADAP PENCEGAHAN RISIKO PENYAKIT JANTUNG KORONER: SYSTEMATIC REVIEW - Irsyadio Raihansa Hadi (2022)
Background: Heart diseases is the leading cause of death in Indonesia and the world, one of the reason for it is Coronary Heart Disease whereas it's a progresitivity of atherom plaque building on coronary artery caused by peroxidation of lipid in blood vessels which induced by free radicals leads to narrowing of blood vessel or even occlusion of a blood vessel. Many efforts on curing and preventing of atherosclerosis progresitivity including the use of herbal plants as an alternative. One of many that had been researched was the use of fermented garlic extract on Coronary heart disease risk prevention. This systematic review was held for analyze the effectivity of using fermented garlic extract on coronary heart disease risk prevention. Methods: A systematic review conducted by starting a literature search from May 2021 to February 2022. The literature that being analyzed was from Google Scholar and PubMed, database using PRISMA-P 2020. Results: processed data from 6 journals finds 4 journals with significant changes of the parameter and 2 journals with insignificant changes of the parameter. Conclusion: the use of fermented garlic extract is effective in risk preventing coronary heart disease. It is based of analyzed journals that there was improvement in parameter used in each journals which related to risk of CHD such as laboratory parameter and quality of life parameters. As for the dose that shows effectivity on risk prevention of coronary heart disease was 2400 mg/day on humans, 900mg/200gWW on male Sprague dawley rats, and 1,38g/WW on wistar rats.